2016
DOI: 10.1597/14-303
|View full text |Cite
|
Sign up to set email alerts
|

Dental Anomalies in a Brazilian Cleft Population

Abstract: The prevalence of dental anomalies in patients with NSCL/P was higher than that reported in overall population. This study found preferential associations between dental anomalies and specific extensions of NSCL/P, suggesting that dental agenesis and ectopic tooth may be part of oral cleft subphenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
3
18
0
1
Order By: Relevance
“…In a study of 240 patients with BCLP 3.8% of patients exhibited oligodontia with upper laterals and upper and lower second premolars most frequently missing. Also of note is a significant incidence of supernumerary teeth in the patients with isolated cleft lip and also in some cases of BCLP [Riis et al, ; Sá et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 240 patients with BCLP 3.8% of patients exhibited oligodontia with upper laterals and upper and lower second premolars most frequently missing. Also of note is a significant incidence of supernumerary teeth in the patients with isolated cleft lip and also in some cases of BCLP [Riis et al, ; Sá et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings suggested that the affected families did not have a higher genetic risk for dental anomalies than the general population and that the higher prevalence of these anomalies was mainly a consequence of various surgical interventions ( 14 ). However, this higher prevalence ( 3 , 11 , 15 , 16 ) of dental anomalies observed in cleft patients has been reported to be related to the existence of a common genetic link between oral clefts and dental anomalies in other studies ( 17 ). For instance, genes whose mutations are associated with tooth agenesis, such as MSX1 and PAX9, also contain single nucleotide polymorphisms as genetic risk factors for orofacial clefts ( 18 ).…”
Section: Discussionmentioning
confidence: 85%
“…A multifactorial model of genetic inheritance has been suggested for nonsyndromic cleft lip and/or palate (NSCL/P) based on the interaction of genetic and environmental factors ( 1 , 2 ). It is very common to observe different kinds of tooth anomalies in children with cleft lip and/or palate (CL/P), such as supernumerary teeth or missing teeth, microdontia, rotated teeth, hypoplasia, transpositions, and root deviation, usually detected on the cleft side ( 3 - 5 ). Tooth anomalies can be a challenge to the multidisciplinary health team treating these patients, but early detection improves treatment outcomes and orthodontic and surgical planning can be properly executed to obtain adequate aesthetic and functional results ( 3 - 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSOC and DA etiologies are attributed to complex interactions between genetic, epigenetic and environmental factors during the process of development 2,4-6 . The association between these congenital anomalies has been initially proposed because individuals with NSOC have a higher prevalence of DA than the general population 7,8 , and later studies demonstrated that genes and pathways related to tooth development are also involved with NSOC, reinforcing the putative link between DA and oral clefting 9,10 . Dental agenesis, supernumerary teeth, microdontia, fused teeth, ectopic eruption, gyroversion, taurodontism and enamel hypoplasia are considerably the more prevalent DA in individuals with NSOC 1,8,[11][12][13][14][15][16][17][18][19] . In addition, the severity these DA seems to be directly related to the severity of the NSOC [11][12][13]20,21 .…”
Section: Introductionmentioning
confidence: 99%